2016
DOI: 10.3109/17435390.2016.1140242
|View full text |Cite
|
Sign up to set email alerts
|

Food web effects of titanium dioxide nanoparticles in an outdoor freshwater mesocosm experiment

Abstract: Over the course of 78 days, nine outdoor mesocosms, each with 1350 L capacity, were situated on a pontoon platform in the middle of a lake and exposed to 0 μg L(-1) TiO2, 25 μg L(-1) TiO2 or 250 μg L(-1) TiO2 nanoparticles in the form of E171 TiO2 human food additive five times a week. Mesocosms were inoculated with sediment, phytoplankton, zooplankton, macroinvertebrates, macrophytes and fish before exposure, ensuring a complete food web. Physicochemical parameters of the water, nutrient concentrations, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The same stock suspension was used in order to provide a more reliable comparison between the previous and present experiments. Previously, we provided a comprehensive physico-chemical characterization of this particular batch of E171 55 . In summary, E171 is at least 99% pure, and has an anatase crystalline structure.…”
Section: Methodsmentioning
confidence: 99%
“…The same stock suspension was used in order to provide a more reliable comparison between the previous and present experiments. Previously, we provided a comprehensive physico-chemical characterization of this particular batch of E171 55 . In summary, E171 is at least 99% pure, and has an anatase crystalline structure.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, studies on the impact of nanoparticles focus mainly on their high bioactivity 17 , which is determined by the following relationship: smaller particles exhibit larger active surface area resulting in higher bioavailability, which ends up in increased toxicity 28,56 . Experiments demonstrated that the toxicity of nanoparticles of a specific chemical composition (usually artificially synthesized compounds) depends on the biology of the plankton species subjected to the toxicological tests and to the environment of the interactions 22,25,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Their reactivity stems not only from the size of the active surface, but also from a substantially larger scale of impact 28,29 . Studies on the influence of nanoparticles upon planktonic invertebrates were carried out with toxicology tests and referred mostly to Cladocera species 22,25,30,31 . Unfortunately, there are no similar studies on zooplankton in natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…The material was in the form of commercial white food coloring (E171) with 99% purity. Detailed characteristics of the nanoparticles were stated in two previous studies that used the same nanomaterial batch [13,37]. Nano-CeO2 with particles <25 nm in diameter were obtained from Sigma Aldrich, USA.…”
Section: Nanoparticlesmentioning
confidence: 99%